Surviving Black Swans II: timing the 2020-2022 roller coaster - Pankaj Topiwala (Journal of Risk and Financial Management, 2023)
Unbeknownst to the public, most investment funds actually underperform the broader market. Yet, millions of individual investors fare even worse, barely treading water. Algorithmic trading now accounts for over 80% of all trades and is the domain of professionals. Can it also help the small investor? In a previous paper, we laid the foundations of a simple algorithmic market timing approach based on the moving average crossover concept which can indeed both outperform the broader market and reduce drawdowns, in a way that even the retail investor can benefit. In this paper, we extend our work to study the recent volatile time period, 2020-2022, and especially the unexpected market roller coaster of 2022, to see how our ideas hold up. While our methods overall would not have made gains in 2022, they would have suffered lessor drawdowns than the market, and made consistent gains over longer periods, including the volatile 2020-2022 period. In addition, at least one of our algorithms would have made handsome profits even in 2022, and can generally negotiate black swans well.
Keywords: 650; algorithm trading; buy-and-hold; index trading; investment; market timing; trading